2013
DOI: 10.1364/oe.21.023231
|View full text |Cite
|
Sign up to set email alerts
|

Modeling electro-optical characteristics of broad area semiconductor lasers based on a quasi-stationary multimode analysis

Abstract: To increase the brightness of broad area laser diodes, it is necessary to tailor the optical properties of their waveguide region. For this purpose, there is the need for simulation tools which can predict the optical properties of the complete device and thus of the outcoupled light. In the present publication, we show a numerical method to calculate typical intensity distributions of the multimode beam inside a high-power semiconductor laser. The model considers effects of mode competition and the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In continuous wave operation it can be observed that the beam quality of the laser degrades at high current densities and temperatures [9]. This phenomenon could not be reproduced by our simulation model in [3], because it did not include the computation of the temperature distribution inside the laser. Therefore, we extended this model with a calculation of the heat sources from the optical simulation as described in section 3.…”
Section: Calculation Model Comprising Thermal Effectsmentioning
confidence: 92%
See 1 more Smart Citation
“…In continuous wave operation it can be observed that the beam quality of the laser degrades at high current densities and temperatures [9]. This phenomenon could not be reproduced by our simulation model in [3], because it did not include the computation of the temperature distribution inside the laser. Therefore, we extended this model with a calculation of the heat sources from the optical simulation as described in section 3.…”
Section: Calculation Model Comprising Thermal Effectsmentioning
confidence: 92%
“…To optimize the lasers and to tailor the microstructures, it is necessary to have an efficient and accurate simulation model to compute the output power and beam quality of the device. In this work we present our latest improvements and enhancements of the simulation method we recently published in [3]. In particular, we show the implementation of a thermal analysis which allows to calculate the influence of the temperature distribution inside the waveguide.…”
Section: Introductionmentioning
confidence: 99%
“…In the latest simulations of such resonators [10], which consider mode competition and nonlinear effects of the gain medium, a similar intensity distribution as measured can be reconstructed numerically.…”
mentioning
confidence: 96%
“…In a future work we will present the possibility to design phase structures with a parameterized nonlinear optimization of the beam quality and efficiency. This optimization is based on the multimode analysis presented in [10]. …”
mentioning
confidence: 99%
“…The large number of high-order lateral modes deteriorates the lateral divergence, hence hindering many underlying applications and limiting the improvement of efficiency. To improve the lateral beam quality of BA diode lasers, numerous methods have been proposed, including a tapered waveguide, 7) tilted cavity, 8) phase structure, 9,10) resonant antiguiding, 11) and external cavity techniques. 12) However, the improvement of lateral beam quality is often accompanied by either sacrificing output power or an increased processing complexity, as well as the cost of these methods.…”
mentioning
confidence: 99%